Rewriting Caesar: Cassius Dio and an Alternative Ethnography of the North - Johnston, Andrew C. (Histos, 2019)
It has gone generally unnoticed in scholarship that Cassius Dio is unique among the Greek writers of the imperial period in not using the ethnic term Γερµανοί to refer to the peoples dwelling east of the Rhine. This paper argues that this absence is a polemical response to the innovative geography of Caesar’s commentarii, and part of a larger project undertaken by Dio to critically rewrite the history of Caesar and reinterpret Roman imperialism in the north. The removal of the Γερµανοί from the map ultimately supports Dio’s attitudes, based on his experience as a senatorial governor, towards contemporary frontier policy.